L’exécution des décisions des juridictions internationales des droits de l’homme: vers une harmonisation des systèmes régionau (2010)
This article, which compares the legal monitoring procedures of the judgments of the European and Inter-American Court of Human Rights, states that these regimes were initially thought of in very diverse terms. Indeed the political approach at the European level is opposed to the judicial approach adopted by the Inter-American system. This study demonstrates how through evolution, which has already occurred in Europe but is still in preparation in America, both regional systems are moving closer together towards a mixed system (judicial and political) involving several organs, at the international and national levels. Facing similar cases of noncompliance (for either technical or political reasons), both systems try to reply through non punitive measures.